Bio-fuel-contaminated lubricant and hardening effects on the friction and wear of AISI 1045 steel - Maleque, Md. Abdul; Masjuki, H.H.; Ishak, M. (Taylor and Francis Inc., 1998)
A study has been made on the wear and fiction of hardened AISI 1045 steel using a pi-pin-ondisc type of fiction and wear apparatus. During the investigation the linear pin wear, coe@cient of friction and rise in pin specimen temperature were monitored and wear and fiction curues 'plotted. Wear sujaces and mechanism were investigated by means of optical microscopy. Analysis of used lubricating oil was pe#~nned using ZTIR spectroscopy. It was shown that the wear rate, type of wear and friction coeficient were influenced by contaminating the lubricant with biefuel as. well as the sutface hardening treatment. Corrosive wear and pits on the specimen sujace were found when plain biefuel was used as lubricating oil. The results also confinned that better wear resistance was obtained from the surface-hardened steel specimen with 4 % biofuel-contaminated lubricant. Results from this study will be useful in material selection for tribological components in diesel engines running on vegetable fuel.